2021
DOI: 10.1002/agt2.16
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid–based aggregates and their biomedical applications

Abstract: The more than three decades of research in nucleic acid nanotechnology has led to the thrilling progress in rationally designed structures and artificial molecular devices with programmable functions and various applications. Nucleic acid–based aggregates feature precise molecular recognition and sequence programmability, versatility, as well as marked biocompatibility, providing promising candidates for biomedical applications. In this minireview, we summarize the recent, successful efforts to construct and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 117 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…211 Further, different types of DNA hydrogels such as pure DNA hydrogels, hybrid hydrogels, and dendritic DNA hydrogels have been determined to exhibit resistance to enzymatic hydrolysis, which may alter the pharmacokinetics. 175,212 Nevertheless, there are only a limited research that have aimed toward understanding this drawback due to limitations in the availability of suitable research tools.…”
Section: Applications Of Dna Bioinks In 3d Bioprintingmentioning
confidence: 99%
“…211 Further, different types of DNA hydrogels such as pure DNA hydrogels, hybrid hydrogels, and dendritic DNA hydrogels have been determined to exhibit resistance to enzymatic hydrolysis, which may alter the pharmacokinetics. 175,212 Nevertheless, there are only a limited research that have aimed toward understanding this drawback due to limitations in the availability of suitable research tools.…”
Section: Applications Of Dna Bioinks In 3d Bioprintingmentioning
confidence: 99%
“…Biomedical application of several polymers, for example, polymeric hydrogel, can be affected by the aggregation effect of polymers. Aggregation is an important process, serving as a widely used fabrication technique for nanomaterials, [ 215 ] such as hydrogels, nanoparticles, and microsponges. [ 216 ] A simple aggregated structure can endow scaffolds with powerful functions, while different aggregated structures can endow scaffolds with various combinations of functions.…”
Section: Conclusion Remarks and Future Perspectivesmentioning
confidence: 99%
“…As one of the most programmable nanomaterials, DNA nanostructures have been widely used in biomedicine and bioimaging fields due to their high biocompatibility and biostability. On the basis of a highly specific and precise Watson–Crick base pairing principle, DNA sequences can be rationally designed into structures with varying dimensions, shapes, and sizes. Numerous studies have recently reported the application of programmable DNA assemblies coupled with enzyme-free signal amplification strategies in the field of miRNA imaging analysis in order to achieve sensitive biosensing and bioimaging. Among them, catalytic hairpin assembly reaction, hybridization chain reaction reaction, entropy-driven circuit reaction, and DNAzyme cleavage signal amplification have been widely used in the enzyme-free signal amplification strategies. …”
Section: Introductionmentioning
confidence: 99%